Body fat and circulating leptin levels in the captive short-beaked echidna (Tachyglossus aculeatus) - Kate J. Dutton-Regester; Alice Roser; Haley Meer; Andrew Hill; Michael Pyne; Aiman Al-Najjar; Tim Whaites; Jane C. Fenelon; Katherine L. Buchanan; Tamara Keeley; Marilyn B. Renfree; Stephen D. Johnston (Journal of Comparative Physiology B, 2024)
It is possible that the reproductive strategy of the short-beaked echidna is related to seasonal changes in fat deposition and energy availability, regulated by seasonal changes in endocrine function. We predicted that circulating leptin levels would be directly proportional to adiposity during most of the year, but that a change in this relationship would occur during the pre-breeding season to allow increased fat deposition. To test this hypothesis, we made use of a captive colony of echidnas to describe and quantify changes in fat distribution and the adipostatic hormone leptin. First we assessed seasonal changes in circulating leptin levels, body mass and adiposity for three male and three female adult echidnas maintained on a standard diet. Second, we explored the relationship between circulating leptin levels and increased caloric intake for an additional five adult female echidnas that were provided with supplemented nutrition. Third we visualised fat distribution in male and female adult echidnas using magnetic resonance imaging (MRI) before and after the breeding season, to determine where fat is deposited in this species. For echidnas maintained on the standard diet, there were no seasonal changes in body mass, body fat or plasma leptin levels. However, female echidnas provided with supplemented nutrition had significantly elevated plasma leptin levels during the breeding season, compared to the pre-and post- breeding periods. MRI showed substantial subcutaneous fat depots extending dorso-laterally from the base of the skull to the base of the tail, in both sexes. Pre-breeding season, both sexes had considerable fat deposition in the pelvic/rump region, whilst the female echidna accumulated most fat in the abdominal region. This study shows that male and female echidnas accumulate body fat in the pelvic/rump and the abdominal regions, respectively and that circulating leptin may promote fattening in female echidnas during the breeding season by means of leptin resistance. However, further research is required to evaluate the precise relationship between seasonal changes in leptin and adiposity.

Correction to: Genetic sex test for the short-beaked echidna (Tachyglossus aculeatus) - Shannon E. Keating; Jane C. Fenelon; Michael Pyne; Brendan J. Pinto; Irán Andira Guzmán-Méndez; Stephen D. Johnston; Marilyn B. Renfree; Tony Gamble (Conservation Genetics Resources, 2022)

Genetic sex test for the short-beaked echidna (Tachyglossus aculeatus) - Shannon E. Keating; Jane C. Fenelon; Michael Pyne; Brendan J. Pinto; Irán Andira Guzmán-Méndez; Stephen D. Johnston; Marilyn B. Renfree; Tony Gamble (Conservation Genetics Resources, 2022)

Coumarins and flavones from the fruit and root extracts of Micromelum integerrimum - Virayu Suthiphasilp; Wisanu Maneerat; Raymond J. Andersen; Stephen G. Pyne; Chatchai Muanprasat; Sawinee Seemakhan; Suparerk Borwornpinyo; Surat Laphookhieo (Natural Product Research, 2019)

Big burns, big questions - Stephen J. Pyne (Ecology, 2018)

Pyrogeography, historical ecology, and the human dimensions of fire regimes - Christopher I. Roos; David M. J. S. Bowman; Jennifer K. Balch; Paulo Artaxo; William J. Bond; Mark Cochrane; Carla M. D'Antonio; Ruth DeFries; Michelle Mack; Fay H. Johnston; Meg A. Krawchuk; Christian A. Kull; et al. (Journal of Biogeography, 2014)
In our 2011 synthesis (Bowman et al ., Journal of Biogeography , 2011, 38 , 2223–2236), we argued for a holistic approach to human issues in fire science that we term ‘pyrogeography’. Coughlan & Petty ( Journal of Biogeography , 2013, 40 , 1010–1012) critiqued our paper on the grounds that our ‘pyric phase’ model was built on outdated views of cultural development, claiming we developed it to be the unifying explanatory framework for all human–fire sciences. Rather, they suggest that ‘historical ecology’ could provide such a framework. We used the ‘pyric transition’ for multiple purposes but did not offer it as an exclusive explanatory framework for pyrogeography. Although ‘historical ecology’ is one of many useful approaches to studying human–fire relationships, scholars should also look to political and evolutionary ecology, ecosystems and complexity theories, as well as empirical generalizations to build an interdisciplinary fire science that incorporates human, ecological and biophysical dimensions of fire regimes.

Pyromancy: Reading Stories in the Flames - STEPHEN J. PYNE (Conservation Biology, 2004)
A consensus history of fire in the United States has emerged over the past decade. It correctly identifies fire suppression's liabilities, while probably over‐enthusing about fire‐science capabilities. What it lacks, however, is a context of the subject's larger, braided narratives. There is, first, the grand story of fire on Earth. Quite apart from active suppression, open fire is disappearing in competition with industrial combustion. Second, there is the peculiar narrative of the public lands, the prime domain for wildland fires. These lands, and the institutions for their management, are rapidly changing. They began as “imperial” institutions, but now are devolving, privatizing, and otherwise decolonizing. Fire will change with those reforms. Third, there is a national narrative, currently obsessed with the collision of the wild and the exurban. This will probably pass within 5–6 years. Finally, there is the evolving narrative of how we imagine fire. We need a truly biological theory of fire, one in which we can flourish as unique fire creatures.